A New Titanosaurian Sauropod from the Hekou Group (Lower Cretaceous) of the Lanzhou-Minhe Basin, Gansu Province, China - Li, Li-Guo (Public Library of Science, 2014)
Increased excavation of dinosaurs from China over the last two decades has enriched the record of Asian titanosauriform sauropods. However, the relationships of these sauropods remain contentious, and hinges on a few well-preserved taxa, such as Euhelopus zdanskyi. Here we describe a new sauropod, Yongjinglong datangi gen. nov. et sp. nov., from the Lower Cretaceous Hekou Group in the Lanzhou Basin of Gansu Province, northwestern China. Yongjinglong datangi is characterized by the following unique combination of characters, including seven autapomorphies: long-crowned, spoon-shaped premaxillary tooth; axially elongate parapophyses on the cervical vertebra; very deep lateral pneumatic foramina on the lateral surfaces of the cervical and cranial dorsal vertebral centra; low, unbifurcated neural spine fused with the postzygapophyses to form a cranially-pointing, triangular plate in a middle dorsal vertebra; an “XI”-shaped configuration of the laminae on the arches of the middle dorsal vertebrae; a very long scapular blade with straight cranial and caudal edges; and a tall, deep groove on the lateral surface of the distal shaft of the radius. The new specimen shares several features with other sauropods: a pronounced M. triceps longus tubercle on the scapula and ventrolaterally elongated parapophyses in its cervical vertebra as in Euhelopodidae. Based on phylogenetic analyses Yongjinglong datangi is highly derived within Titanosauria, which suggests either a remarkable convergence with more basal titanosauriform sauropods in the Early Cretaceous or a retention of plesiomorphic features that were lost in other titanosaurians. The morphology and remarkable length of the scapulocoracoid reveal an unusual relationship between the shoulder and the middle trunk: the scapulocoracoid spans over half of the length of the trunk. The medial, notch-shaped coracoid foramen and the partially fused scapulocoracoid synostosis suggest that the specimen is a subadult individual. This specimen sheds new light on the diversity of Early Cretaceous Titanosauriformes in China.